The EFL Students Internal Factor Causing Critical Listening Anxiety at IAIN Palangka Raya - Firman Billy Fanandi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
In learning, worry and anxiety are natural things experienced by humans. In the same vein, anxiety can be caused by obstacles in the process of learning to listen. This happens to students to master listening skills. Therefore, this study aims to determine the factors that influence students' listening anxiety in the Critical Listening class at the State Islamic Institute of Palangka Raya. To answer this question, the researcher used mixed methods. Participants in this study amounted to 51 participants. Researchers distributed questionnaires and conducted interviews with participants. Based on the findings, there are two factors that influence students' listening anxiety. The first factor was the tension and concern of English to listen to audio. The second factor was lack of confidence in listening to audio